OmpW overexpression in meropenem-exposed Acinetobacter baumannii persister cells enhances virulence and reveals a candidate target - Liu, Bin; Wang, Junan; Hu, Jincheng; Li, Liang; Liu, Lei (Frontiers in Microbiology, 2025)
ObjectiveAcinetobacter baumannii is one of the most drug-resistant microorganisms in hospital-acquired infections. The treatment of choice for A. baumannii infections is carbapenems (e.g., meropenem). However, A. baumannii can develop resistance to all clinical antibiotics associated with the formation of persister cells. We first assessed the virulence and differential expression levels of outer membrane protein W (OmpW) in A. baumannii persister cells and A. baumannii regular cells in vivo and in vitro after exposure to meropenem.MethodsPersister cells were confirmed using a standard method. OmpW characterization was performed using western blot analysis, and OmpW expression was detected using real-time polymerase chain reaction (PCR) after ribonucleic acid (RNA) extraction. An A. baumannii virulence assay was performed using the Galleria mellonella larvae model. Relative expression was calculated using the 2−ΔΔCT method.ResultsThe presence of bona fide A. baumannii persister cells was confirmed after 48 h of meropenem exposure at 15 μg/mL, with levels reaching 0.3216% of the initial bacterial population and a survival fraction of 0.081%. OmpW genes were highly expressed at more than 2.68-fold (p = 0.01) with meropenem exposure at 1 μg/mL and 8.61-fold (p = 0.0005) with meropenem exposure at 15 μg/mL. There was a significant difference in the lethal dose 50% (LD50) at 24 h postinfection between persister cells (2.01 × 105 CFU/larva) and regular cells (4.73 × 105 CFU/larva) at p < 0.05. Similarly, there was a significant difference between the LD50 at 48 h for persister cells (1.61 × 105 CFU/larva) and regular cells (4.08 × 105 CFU/larva) at p < 0.05. However, there was no statistically significant difference in the LD50 at 72, 96, and 120 h postinfection.ConclusionOmpW overexpression in meropenem-exposed A. baumannii persister cells enhances virulence and reveals a candidate target for preventing and controlling A. baumannii persister cells.